An examination of television advertising production in selected OIC countries using a hierarchy of influences model - Mokhtar, Aida (2017)
There have been several research studies examining television advertising content in terms of effects rather than television advertising production. The production process is significant to examine so as to determine the factors that influence advertising messages prior to the formation of a framework guiding the television advertising production process. The purpose of the research study is to examine the television advertising production process of countries that are members of the Organisation of Islamic Cooperation (OIC). The OIC acts as a collective voice for Muslims making its members important to examine in relation to whether Islamic values are imbued in the production of television advertisements. The study was framed using the Hierarchy of Influences model that underlines the five levels of influence on media content ranging from macro to micro levels that include social systems, social institutions, organizations, routines, and individuals. Interviews with thirty two representatives of OIC countries were carried out and the data was analysed using thematic analysis as the first layer of Fairclough’s 3D critical discourse analysis model. The findings suggest that television advertising production is influenced by the countries’ different subsystems involving an assortment of economic, political, cultural dimensions; government television media prefer disseminating public communication messages to audience members; the media as a social institution can be more prominently Islamic in some countries than others thus this fashions different advertising content; the government plays a more or less prominent role in regulating the advertisements; and the absence of guidelines that scrutinise television advertising production by OIC countries is apparent. A television advertising framework is recommended as the outcome of the research study by focusing on the ideals and commonalities between OIC countries.